CARIES PREVENTION AMONG JUNIOR SCHOOLCHILDREN - S.К. Matelo; T.V. Kupets; L.N. Polyanskaya (Вопросы современной педиатрии, 2011)
Biennial program of controlled tooth brushing performed econdary school among junior schoolchildren from Minsk secondary school № 166 proved to be highly effective. Decrease in caries increment has been shown on the average up to 50%. No credible differences between remineralising defluorinated toothpastes or pastes enriched with aminofluoride (F = 500 ppm) and sodium fluoride  (F = 1000 ppm) efficacy were found in this study. Credibility of the results was determined by comparison with similar study conducted on a bigger population of children. Though anti-caries effect of the same tooth-pastes in a bigger-scale study was lower — within 30%. Such difference can be explained by a different level of motivation and discipline of participants.Key words: schoolchildren, dental caries prevention, toothpastes. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (6): 48–51)